The effect of brand image, brand trust, and brand experience on consumers' intention to purchase hedonic products in South Africa - Durand, Kyle (My University, 2015)
Whilst there are extensive prior studies on the drivers of consumers’ intention to purchase a product, such prior studies have tended to look at developed markets (Cobb-Walgren, Ruble, & Donthu, 1995; O'brien, 1971; Philiastides & Ratcliff, 2013) In South Africa, there is limited researches on hedonic products and consumers decision making when purchasing these products. The purpose of this research is to determine the effect that brand image, trust and experience has on consumers’ intention to purchase hedonic products in South Africa. The hypothesised relationship between these predictor variables (brand image, brand trust and brand experience) against the outcome variable of a consumer’s intention to purchase was postulated. The method of analysis used was quantitative. This tactic is a convenience sampling tactic which is utilised frequently within social research (Bickman & Rog, 1998) The initial pool of contacts was that ere utilised as part of the snowballing technique was 162. Path analysis was utilised to assess the relationship between the manifest variable and the outcome variable. Brand image and Brand experience of hedonic products has a significant and positive effect on consumer’s intention to purchase. Brand experience was shown to have a higher effect than brand trust on the consumer’s intention to purchase. The Brand image constructed was rejected. These constructs are important for markers to understand within emerging markets as Sharma (2011) noted the growing materialism in emerging economies as opposed to the slowing down of materialism in the developed world. Shukla (2012) furthermore highlighted the importance of understanding this market as emerging markets size and growth provides large opportunities for firms.
MBA
Keywords: Brand choice -- South Africa. Consumer behavior -- South Africa. Consumers' preferences -- South Africa.